Solid electrolyte and its preparation method and application

By doping magnesium to the solid electrolyte Li1+2xMgxGe2-xP3O12 of hexahedral GeO6, the problems of flammability and low ionic conductivity in lithium-ion batteries are solved, and high-temperature stability and safety performance are improved. It is suitable for all-solid lithium batteries. and lithium-ion batteries.

CN115295873BActive Publication Date: 2024-12-13NAYUAN NEW MATERIAL TECH (WUXI) CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202211022260.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-28
Publication Date
2024-12-13
Estimated Expiration
2042-08-28

AI Technical Summary

Technical Problem

The liquid organic electrolytes in existing lithium-ion batteries are flammable and easy to leak, and the gel-like polymer electrolytes still have flammable characteristics, resulting in frequent fire accidents and poor ionic conductivity of solid electrolytes, making it difficult to effectively solve safety problems.

Method used

The solid electrolyte Li1+2xMgxGe2-xP3O12 doped in hexahedral GeO6 is used to obtain a solid electrolyte with high ionic conductivity and structural stability through a specific preparation method, which is suitable as an electrolyte membrane or separator material for lithium batteries.

Benefits of technology

It achieves structural stability and safety performance under high temperature conditions, improves the ionic conductivity of lithium-ion batteries, reduces fire risks, and is suitable for all-solid-state lithium batteries and lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115295873B_ABST
    Figure CN115295873B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of solid-state battery technology, and specifically provides a solid electrolyte and a preparation method and application thereof. The solid electrolyte has the following general formula: Li 1+2x Mg x Ge 2‑x P3O 12 ; wherein x is any value from 0 to 0.5, and x is not 0. The solid electrolyte provided by the present invention has high ionic conductivity and is non-flammable, so when made into a solid electrolyte membrane, it can effectively improve the ionic conductivity and safety of the all-solid-state lithium battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solid-state batteries, and in particular relates to a solid-state electrolyte and a preparation method and application thereof. Background Art

[0002] In the current commercial lithium-ion batteries, the electrolytes mainly include liquid organic electrolytes and gel polymer electrolytes. Liquid organic electrolytes are flammable and easy to leak because they contain organic matter. When the battery is thermally runaway, the liquid electrolyte will react with the high-energy electrode material, releasing a large amount of heat, causing the battery to burn and explode; while the gel polymer electrolyte is safer than the liquid electrolyte, but the electrolyte still contains high molecular polymers, so it is still flammable. Because of the above reasons, fire accidents caused by lithium-ion batteries occur from time to time, and lithium-ion battery fires are more difficult to control than ordinary fires, which will cause huge losses to people's lives and property. Therefore, it is very necessary to solve the safety problem of lithium-ion batteries. For this reason, it is proposed to use solid electrolytes to replace the existing organic liquid electrolytes, but the current solid electrolytes generally have the problem of poor ionic conductivity. Summary of the invention

[0003] In view of the safety issues of current organic liquid electrolytes and the poor ion conductivity of solid electrolytes, the present invention provides a solid electrolyte and a preparation method and application thereof.

[0004] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:

[0005] A solid electrolyte having the following general formula:

[0006] Li 1+2x Mg x Ge 2-x P3O 12 ;

[0007] Here, x can be any value between 0 and 0.5, and x does not take the value of 0.

[0008] Furthermore, the solid electrolyte comprises:

[0009] Li 1.1 Mg 0.05 Ge 1.95 P3O 12 , Li 1.2 Mg 0.1 Ge 1.9 P3O 12 , Li 1.4 Mg 0.2 Ge 1.8 P3O 12, Li 1.6 Mg 0.3 Ge 1.7 P3O 12 , Li 2.0 Mg 0.5 Ge 1.5 P3O 12 At least one of .

[0010] Furthermore, the solid electrolyte belongs to the trigonal crystal system, Ge and O are combined to form hexahedral GeO6, and Mg replaces part of Ge in the GeO6.

[0011] Compared with the prior art, the solid electrolyte provided in the embodiment of the present invention has magnesium doped into the hexahedral GeO6 and replaces part of Ge, so it has higher ionic conductivity. At the same time, the material has good structural stability and can still maintain good structural stability under high temperature conditions. It is non-flammable and non-combustible and has higher safety performance. It is suitable as an electrolyte membrane for solid-state lithium batteries, etc.

[0012] Correspondingly, an embodiment of the present invention also provides a method for preparing the above-mentioned solid electrolyte.

[0013] Specifically, the preparation method of the solid electrolyte comprises the following steps:

[0014] Mixing a lithium source, a magnesium source, a germanium source and a phosphorus source containing a phosphate group to obtain a first mixed material;

[0015] The first mixed material is dried, and then heated to 400°C to 450°C at a heating rate of 3 to 8°C / min, and kept at 400°C to 450°C for 1 to 5 hours, and then heated to 1300°C to 1450°C at a heating rate of 5 to 20°C / min, and kept at 1300°C to 1450°C until the first mixed material is completely melted;

[0016] Cooling to room temperature to obtain a glassy material;

[0017] The glassy material is annealed to obtain a solid electrolyte.

[0018] Furthermore, the lithium source, the magnesium source, the germanium source and the phosphate-containing phosphorus source are mixed according to a ratio of the amount of substance of lithium:magnesium:germanium:phosphate=k×(1+2x):x:(2-x):3, wherein x takes any value between 0 and 0.5, and x does not take the value of 0, and the coefficient k takes any value between 1 and 1.1.

[0019] Furthermore, the annealing temperature is 550° C. to 1050° C.; and / or the cooling process is quenching.

[0020] Furthermore, the annealing temperature is 600°C to 650°C.

[0021] Furthermore, the lithium source is selected from at least one of lithium carbonate, lithium hydroxide, lithium oxalate, lithium nitrate, and lithium bicarbonate;

[0022] The magnesium source is selected from at least one of magnesium carbonate, magnesium oxide, magnesium hydroxide, magnesium bicarbonate, magnesium acetate, and magnesium oxalate;

[0023] The germanium source is selected from at least one of germanium dioxide, germanium monoxide, germanium tetrahydroxide, germanium nitrate, germanium oxalate, and germanium bicarbonate;

[0024] The phosphate-containing phosphorus source is selected from at least one of diammonium phosphate, triammonium phosphate, diammonium hydrogen phosphate, phosphorus pentoxide, and phosphorus trioxide.

[0025] The preparation method of the solid electrolyte provided by the embodiment of the present invention has the advantages of simple process and good process stability, and can obtain a solid electrolyte with a crystal structure, and the purity of the solid electrolyte is high. Magnesium is doped into the hexahedral GeO6 and replaces part of Ge, so that the obtained solid electrolyte also has high ionic conductivity and good structural stability.

[0026] Furthermore, the embodiments of the present invention also provide the use of the above-mentioned solid electrolyte as a component of an all-solid-state lithium battery electrolyte membrane or a component of a lithium-ion battery separator coating or an all-solid-state lithium battery positive electrode and / or negative electrode additive. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0028] Figure 1 XRD patterns of the solid electrolytes and LGP comparison samples provided in Examples 1 to 5 of the present invention;

[0029] Figure 2 XRD patterns of the solid electrolytes provided in Examples 3, 6 to 9 of the present invention;

[0030] Figure 3 The DSC graph of the intermediate product without annealing treatment provided in Example 3 of the present invention;

[0031] Figure 4 Room temperature static temperature of the solid electrolyte provided by Example 4 of the present invention and the comparative sample LAGP-05 7Solid-state nuclear magnetic (SS-NMR) spectrum of Li-NMR;

[0032] Figure 5 The low temperature (166K) of Example 4 of the present invention and the comparative sample LAGP-05 6 Li-MAS-NMR spectrum;

[0033] Figure 6 The room temperature of Example 4 and the comparative sample LAGP-05 31 P-MAS-NMR spectrum;

[0034] Figure 7 The solid nuclear magnetic resonance of Example 4 of the present invention 31 P-MAS-NMR (room temperature) test peak curve;

[0035] Figure 8 Solid-state NMR of LAGP-05 31 P-MAS-NMR (room temperature) test peak curve;

[0036] Fig. 9 The room temperature of the solid electrolyte provided by Examples 3, 6 to 9 of the present invention 31 P-MAS-NMR (left) and room temperature static 7 Li-NMR (right) test spectrum;

[0037] Fig.10 The ionic conductivity curves of the solid electrolytes of Examples 3 and 9 of the present invention, the solid electrolyte membrane of Application Example 1, and the comparative sample LGP;

[0038] Fig.11 This is a high temperature cycle curve of a solid-state lithium battery provided in Application Example 2 of the present invention. DETAILED DESCRIPTION

[0039] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0040] The embodiment of the present invention provides a solid electrolyte having a chemical formula as shown in Formula I: Li 1+2x Mg x Ge 2- x P3O 12...(I), hereinafter referred to as LMGP; wherein x is any value from 0 to 0.5, and x does not take a value of 0. The solid electrolyte provided in this embodiment is non-flammable and has good stability at high temperatures, and can effectively solve the safety problems caused by the liquid electrolyte of lithium-ion batteries. At the same time, the solid electrolyte of the embodiment of the present application has good mechanical properties, a simple preparation process, and a high material utilization rate.

[0041] The solid electrolyte provided in the embodiment of the present invention belongs to the trigonal system, and Ge and O are combined to form hexahedral GeO6, and the doped Mg replaces part of the Ge in the GeO6. Since Mg replaces part of the Ge in the GeO6, the obtained solid electrolyte LMGP has a NASICON structure.

[0042] In some embodiments, the solid electrolyte includes Li 1.1 Mg 0.05 Ge 1.95 P3O 12 , Li 1.2 Mg 0.1 Ge 1.9 P3O 12 , Li 1.4 Mg 0.2 Ge 1.8 P3O 12 , Li 1.6 Mg 0.3 Ge 1.7 P3O 12 , Li 2.0 Mg 0.5 Ge 1.5 P3O 12 At least one of .

[0043] Based on the above-mentioned solid electrolyte, an embodiment of the present invention further provides a method for preparing the above-mentioned solid electrolyte.

[0044] Specifically, the preparation method of the solid electrolyte comprises the following steps:

[0045] (1) A lithium source, a magnesium source, a germanium source and a phosphorus source containing a phosphate group are mixed to obtain a first mixed material.

[0046] In step (1), a lithium source, a magnesium source, a germanium source and a phosphorus source containing phosphate are mixed in a ratio of lithium: magnesium: germanium: phosphate = k×(1+2x): x: (2-x): 3, wherein x is any value between 0 and 0.7, and x is not 0, and the coefficient k is any value between 1 and 1.1. The coefficient k in the lithium source is a positive number not less than 1, which means that the amount of lithium source added during the preparation process can be slightly excessive.

[0047] In some embodiments, the lithium source is selected from at least one of lithium carbonate, lithium hydroxide, lithium oxalate, lithium nitrate, and lithium bicarbonate; the magnesium source is selected from at least one of magnesium carbonate, magnesium oxide, magnesium hydroxide, magnesium bicarbonate, magnesium acetate, and magnesium oxalate; the germanium source is selected from at least one of germanium dioxide, germanium monoxide, germanium tetrahydroxide, germanium nitrate, germanium oxalate, and germanium bicarbonate; the phosphate-containing phosphorus source is selected from at least one of diammonium phosphate (NH4H2PO4), triammonium phosphate, diammonium hydrogen phosphate, phosphorus pentoxide, and phosphorus trioxide.

[0048] In some embodiments, when the lithium source, magnesium source, germanium source and sulfate-containing phosphorus source are mixed, the mixture is crushed so that the lithium source, magnesium source, germanium source and sulfate-containing phosphorus source are completely crushed into powder, which is conducive to obtaining a uniformly mixed first mixed material. For example, the mixing can be performed using a ball mill, a planetary ball mill, etc.

[0049] (2) The first mixed material obtained in step (1) is dried, and then heated to 400°C to 450°C at a heating rate of 3 to 8°C / min, and kept at 400°C to 450°C for 1 h to 5 h, and then heated to 1300°C to 1450°C at a heating rate of 5 to 20°C / min, and kept at 1300°C to 1450°C until the first mixed material is completely melted.

[0050] In step (2), when the first mixed material is dried, the temperature is 150°C to 220°C, and the drying time is 15h to 25h. By drying, the moisture contained in the raw materials is evaporated to avoid the influence of excessive moisture content on the heating and sintering of the solid electrolyte. Of course, it is also possible to dry each raw material before obtaining the first mixed material, and dry it again after obtaining the first mixed material. In some embodiments, when the constant temperature is maintained at 1300°C to 1450°C, the constant temperature time is 1h to 3h, so that the powder of the first mixed material can be completely melted.

[0051] (3) Cooling to room temperature to obtain a glassy material.

[0052] In step (3), the cooling method is quenching. During the quenching process, the molten first mixed material is passed into a metal block or metal plate surface or a metal container at room temperature and resistant to high temperatures, and the temperature is reduced by rapid heat conduction to obtain a glassy material. In some embodiments, a cooling liquid flow is passed into the metal block or metal plate or the outer surface of the metal container to improve the quenching efficiency and the purity of the obtained glassy material. In some embodiments, the metal block or metal plate has two opposite surfaces, one of which is introduced with the molten first mixed material, and the other surface is in contact with the flowing cooling liquid flow, which is conducive to quenching and heat dissipation.

[0053] (4) Annealing the glassy material obtained in step (3) to obtain a solid electrolyte.

[0054] In step (4), the annealing temperature is 550°C to 1050°C, and the annealing time is 3h to 15h, thereby obtaining a solid electrolyte with high purity. In some embodiments, the annealing temperature is 600°C to 650°C, and a solid electrolyte with uniform crystal form and high purity can be obtained.

[0055] The solid electrolyte provided by the above embodiment of the present invention, or the solid electrolyte prepared by the above preparation method, can be directly used as a component of the solid electrolyte membrane in an all-solid-state lithium battery, or as a coating component of the separator in a lithium-ion battery, or as an additive to at least one of the positive electrode and the negative electrode in an all-solid-state lithium battery. Among them, when used as a coating of the separator in a lithium-ion battery, the lithium ion conductivity can be effectively improved; when used as an additive to the positive electrode and the negative electrode of an all-solid-state lithium battery, the ion conductivity of the electrode can also be effectively improved.

[0056] When used as a component of a solid electrolyte membrane in an all-solid-state lithium battery, the solid electrolyte needs to be prepared into a solid electrolyte membrane. Therefore, the embodiment of the present invention further provides a method for preparing a solid electrolyte membrane based on the above-mentioned solid electrolyte.

[0057] Specifically, the method for preparing the solid electrolyte membrane comprises the following steps:

[0058] (5) Mixing a lithium salt, a lithium salt solvent, the solid electrolyte described above, and an organic solvent to obtain a colloid.

[0059] In step (5), the solid electrolyte: lithium salt additive: lithium salt is dissolved in an organic solvent in a ratio of 0.1 to 3: 15 to 20: 1. The amount of the organic solvent is such that the various substances are mixed to form a slurry, and the solid content of the slurry is 70% to 85%. In some embodiments, the lithium salt solvent includes at least one of polyethylene oxide (PEO), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), polypropylene oxide (PPO), polyvinyl chloride (PVC), and polyvinylidene fluoride (PVDF). When the lithium salt solvent forms a solid electrolyte membrane, the lithium salt can be solvated so that it can be evenly dispersed. In addition, it also acts as a binder to improve the structural strength of the solid electrolyte membrane. In some embodiments, the lithium salt includes at least one of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(difluorosulfonyl)imide (LIFSI), lithium difluorooxalate borate (LIF2OB or LiODFB), lithium trifluoromethanesulfonate (LiOTf), lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), and lithium dioxalate borate (LiBOB). In some embodiments, the organic solvent is selected from at least one of acetonitrile, chloroform, tetrahydrofuran, and anisole.

[0060] (6) Perform aging treatment on the colloid after sealing.

[0061] In step (6), the aging treatment temperature is 50°C to 100°C, and the aging treatment time is 24h to 72h. After aging, the various components of the colloid are evenly distributed, effectively preventing the components from stratification or agglomeration, and obtaining a colloid with uniform phase, which is conducive to obtaining a solid electrolyte membrane with relatively uniform mass density.

[0062] (7) The aged gel is hot-pressed to form a film to obtain a solid electrolyte membrane.

[0063] In step (7), during the hot pressing film forming process, a hot press machine can be used for hot pressing film forming. In some embodiments, the hot pressing temperature of the hot pressing film forming is 50°C to 100°C. After hot pressing, the thickness of the obtained solid electrolyte membrane is between 10μm and 200μm, and the components in the solid electrolyte membrane are evenly distributed. In some embodiments, under the condition of a hot pressing temperature of 50°C to 100°C, two hot pressing processes are performed, namely, hot pressing for 10min to 30min at a pressure of 10bar to 30bar and hot pressing for 5min to 15min at a pressure of 15bar to 50bar, and the pressure of the previous hot pressing is less than the pressure of the next hot pressing. Controlling the pressure of the previous hot pressing to be less than the pressure of the next hot pressing is conducive to the deformation process of the hot pressing film forming process, obtaining a dense solid electrolyte membrane, and reducing the presence of internal closed voids, semi-closed voids, etc. in the solid electrolyte membrane. In addition, during the hot pressing process, the organic solvent volatilizes.

[0064] According to the preparation method of the above-mentioned solid electrolyte membrane, a solid electrolyte membrane is obtained, which contains a lithium salt solvent, a lithium salt and a solid electrolyte, and the lithium salt solvent, the lithium salt and the solid electrolyte are uniformly dispersed, flexible, and have good mechanical properties such as good puncture resistance and tensile strength and excellent ionic conductivity. The solid electrolyte membrane can be directly used in a solid-state lithium battery to isolate the positive electrode sheet and the negative electrode sheet. Especially when the lithium salt solvent is PEO, the improvement effect on the interface problem between the solid electrolyte membrane and the positive electrode sheet and the negative electrode sheet is more obvious, and the interface impedance can be significantly reduced. Because if there is no lithium salt solvent, there are two rigid interfaces between the solid electrolyte and the electrode (including the positive electrode sheet and the negative electrode sheet), which will cause the interface impedance to be extremely large, and the introduction of lithium salt solvents can improve the interface contact problem.

[0065] Based on the solid electrolyte membrane provided above, the embodiment of the present invention further provides a solid lithium battery. In some embodiments, the solid lithium battery includes a positive electrode sheet, a negative electrode sheet and the above-mentioned solid electrolyte membrane, and the solid electrolyte membrane is provided between the positive electrode sheet and the negative electrode sheet to separate the positive electrode sheet and the negative electrode sheet, and prevent the positive electrode sheet and the negative electrode sheet from directly contacting and short-circuiting. In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer attached to the surface of the positive electrode current collector, wherein the positive electrode current collector is selected from aluminum foil, the positive electrode active material layer contains a positive electrode active material, and the positive electrode active material is selected from any one of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, nickel cobalt manganese oxide, and lithium titanate. The positive electrode active material layer also contains a positive electrode binder and a positive electrode conductive agent, wherein the positive electrode binder is selected from PVDF, and the positive electrode conductive additive is selected from carbon black, acetylene black, Super P, etc. In some embodiments, in the positive electrode active material layer, the mass ratio of positive electrode active material: positive electrode binder: positive electrode conductive agent = 8:1:1. In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer attached to the surface of the negative electrode current collector, wherein the negative electrode current collector is selected from copper foil, and the negative electrode active material layer contains a negative electrode active material and a negative electrode binder, wherein the negative electrode active material is selected from any one of artificial graphite, natural graphite, etc., and the negative electrode binder is selected from PVDF. In some embodiments, in the negative electrode active material layer, according to the mass ratio, the negative electrode active material: the negative electrode binder = 9:1.

[0066] In order to more effectively illustrate the technical solution of the present invention, further explanation is given below through multiple specific embodiments.

[0067] Example 1

[0068] A method for preparing a solid electrolyte comprises the following steps:

[0069] Li2CO3, MgO, GeO2, and NH4H2PO4 are mixed and ground evenly according to a molar ratio of Li2CO3:MgO:GeO2:NH4H2PO4=1.1:0.1:3.9:6 to obtain a first mixed material in a powder state;

[0070] Drying the first mixed material at 200° C. for 20 h;

[0071] Then, the temperature was raised to 450°C at a heating rate of 5°C / min and maintained for 2 hours to release the volatile matter; the temperature was further raised to 1350°C at a heating rate of 15°C / min and maintained for 1 hour to melt all the raw materials;

[0072] The molten material is poured onto the surface of a metal block at room temperature for quenching to obtain a glassy material;

[0073] The glassy material was annealed at 600° C. for 5 hours to obtain a first sample.

[0074] The first sample was subjected to XRD analysis, and the results were as follows: Figure 1 As shown. Figure 1 It can be seen that the chemical formula of the first sample obtained is Li 1.1 Mg 0.05 Ge 1.95 P3O 12 .

[0075] Example 2

[0076] A method for preparing a solid electrolyte comprises the following steps:

[0077] Li2CO3, MgO, GeO2, and NH4H2PO4 are mixed and ground evenly according to a molar ratio of Li2CO3:MgO:GeO2:NH4H2PO4=0.6:0.1:1.9:3 to obtain a first mixed material, wherein the first mixed material is in a powder state;

[0078] Drying the first mixed material at 200° C. for 20 h;

[0079] Then, the temperature was raised to 450°C at a heating rate of 5°C / min and maintained for 2 hours to release the volatile matter; the temperature was further raised to 1350°C at a heating rate of 15°C / min and maintained for 1 hour to melt all the raw materials;

[0080] The molten material is poured onto the surface of a metal block at room temperature for quenching to obtain a glassy material;

[0081] The glassy material was annealed at 600° C. for 5 h to obtain a second sample.

[0082] The second sample was subjected to XRD analysis, and the results were as follows: Figure 1 As shown. Figure 1 It can be seen that the second sample has a sharp characteristic peak of the crystal structure, and its chemical formula is Li 1.2 Mg 0.1 Ge 1.9 P3O 12 .

[0083] Example 3

[0084] A method for preparing a solid electrolyte comprises the following steps:

[0085] Li2CO3, MgO, GeO2, and NH4H2PO4 are mixed and ground evenly in a ratio of Li2CO3:MgO:GeO2:NH4H2PO4=0.7:0.2:1.8:3 to obtain a first mixed material in a powder state;

[0086] Drying the first mixed material at 200° C. for 20 h;

[0087] Then, the temperature was raised to 450°C at a heating rate of 5°C / min and maintained for 2 hours to release the volatile matter; the temperature was further raised to 1350°C at a heating rate of 15°C / min and maintained for 1 hour to melt all the raw materials;

[0088] The molten material is poured onto the surface of a metal block at room temperature for quenching to obtain a glassy material;

[0089] Part of the obtained glassy material was annealed at 600° C. for 5 h to obtain a third sample.

[0090] The third sample was subjected to XRD analysis, and the results were as follows: Figure 1 As shown. Figure 1 It can be seen that the third sample has characteristic peaks of crystal structure, and its chemical formula is Li 1.4 Mg 0.2 Ge 1.8 P3O 12 .

[0091] Example 4

[0092] A method for preparing a solid electrolyte comprises the following steps:

[0093] Li2CO3, MgO, GeO2, and NH4H2PO4 are mixed and ground evenly in a ratio of Li2CO3:MgO:GeO2:NH4H2PO4=0.8:0.3:1.7:3 to obtain a first mixed material in a powder state;

[0094] Drying the first mixed material at 200° C. for 20 h;

[0095] Then, the temperature was raised to 450°C at a heating rate of 5°C / min and maintained for 2 hours to release the volatile matter; the temperature was further raised to 1350°C at a heating rate of 15°C / min and maintained for 1 hour to melt all the raw materials;

[0096] The molten material is poured onto the surface of a metal block at room temperature for quenching to obtain a glassy material;

[0097] The glassy material was annealed at 600° C. for 5 h to obtain a fourth sample.

[0098] The fourth sample was subjected to XRD detection and analysis, and the results were as follows: Figure 1 As shown. Figure 1 It can be seen that the fourth sample has a sharp crystal structure characteristic peak, and its chemical formula is Li 1.6 Mg 0.3 Ge 1.7 P3O 12 .

[0099] Example 5

[0100] A method for preparing a solid electrolyte comprises the following steps:

[0101] Li2CO3, MgO, GeO2, and NH4H2PO4 are mixed and ground evenly according to a molar ratio of Li2CO3:MgO:GeO2:NH4H2PO4=1.0:0.5:1.5:3 to obtain a first mixed material in a powder state;

[0102] Drying the first mixed material at 200° C. for 20 h;

[0103] Then, the temperature was raised to 450°C at a heating rate of 5°C / min and maintained for 2 hours to release the volatile matter; the temperature was further raised to 1350°C at a heating rate of 15°C / min and maintained for 1 hour to melt all the raw materials;

[0104] The molten material is poured onto the surface of a metal block at room temperature for quenching to obtain a glassy material;

[0105] The glassy material was annealed at 600° C. for 5 hours to obtain a fifth sample.

[0106] The fifth sample was subjected to XRD analysis, and the results were as follows: Figure 1 As shown. Figure 1 It can be seen that the chemical formula of the fifth sample is mainly Li 2.0 Mg 0.5 Ge 1.5 P3O 12 , and contains some impurities.

[0107] Example 6

[0108] A method for preparing a solid electrolyte comprises the following steps:

[0109] Li2CO3, MgO, GeO2, and NH4H2PO4 are mixed and ground evenly in a ratio of Li2CO3:MgO:GeO2:NH4H2PO4=0.7:0.2:1.8:3 to obtain a first mixed material in a powder state;

[0110] Drying the first mixed material at 200° C. for 20 h;

[0111] Then, the temperature was raised to 450°C at a heating rate of 5°C / min and maintained for 2 hours to release the volatile matter; the temperature was further raised to 1350°C at a heating rate of 15°C / min and maintained for 1 hour to melt all the raw materials;

[0112] The molten material is poured onto the surface of a metal block at room temperature for quenching to obtain a glassy material;

[0113] The glassy material was annealed at 550° C. for 5 hours to obtain a sixth sample.

[0114] The sixth sample was subjected to XRD analysis, and the results were as follows: Figure 2 As shown. Figure 2 It can be seen that the sixth sample is still in a vitrified state and has not crystallized.

[0115] Example 7

[0116] A method for preparing a solid electrolyte comprises the following steps:

[0117] Li2CO3, MgO, GeO2, and NH4H2PO4 are mixed and ground evenly in a ratio of Li2CO3:MgO:GeO2:NH4H2PO4=0.7:0.2:1.8:3 to obtain a first mixed material in a powder state;

[0118] Drying the first mixed material at 200° C. for 20 h;

[0119] Then, the temperature was raised to 450°C at a heating rate of 5°C / min and maintained for 2 hours to release the volatile matter; the temperature was further raised to 1350°C at a heating rate of 15°C / min and maintained for 1 hour to melt all the raw materials;

[0120] The molten material is poured onto the surface of a metal block at room temperature for quenching to obtain a glassy material;

[0121] The glassy material was annealed at 650° C. for 5 h to obtain the seventh sample.

[0122] The seventh sample was subjected to XRD analysis, and the results were as follows: Figure 2 As shown. Figure 2 It can be seen that the chemical formula of the seventh sample is Li 1.4 Mg 0.2 Ge 1.8 P3O 12 .

[0123] Example 8

[0124] A method for preparing a solid electrolyte comprises the following steps:

[0125] Li2CO3, MgO, GeO2, and NH4H2PO4 are mixed and ground evenly in a ratio of Li2CO3:MgO:GeO2:NH4H2PO4=0.7:0.2:1.8:3 to obtain a first mixed material in a powder state;

[0126] Drying the first mixed material at 200° C. for 20 h;

[0127] Then, the temperature was raised to 450°C at a heating rate of 5°C / min and maintained for 2 hours to release the volatile matter; the temperature was further raised to 1350°C at a heating rate of 15°C / min and maintained for 1 hour to melt all the raw materials;

[0128] The molten material is poured onto the surface of a metal block at room temperature for quenching to obtain a glassy material;

[0129] The glassy material was annealed at 750° C. for 5 hours to obtain the eighth sample.

[0130] The eighth sample was subjected to XRD analysis, and the results were as follows: Figure 2 As shown. Figure 2 It can be seen that the chemical formula of the eighth sample is mainly Li 1.4 Mg 0.2 Ge 1.8 P3O 12 , and contains some impurities.

[0131] Example 9

[0132] A method for preparing a solid electrolyte comprises the following steps:

[0133] Li2CO3, MgO, GeO2, and NH4H2PO4 are mixed and ground evenly in a ratio of Li2CO3:MgO:GeO2:NH4H2PO4=0.7:0.2:1.8:3 to obtain a first mixed material in a powder state;

[0134] Drying the first mixed material at 200° C. for 20 h;

[0135] Then, the temperature was raised to 450°C at a heating rate of 5°C / min and maintained for 2 hours to release the volatile matter; the temperature was further raised to 1350°C at a heating rate of 15°C / min and maintained for 1 hour to melt all the raw materials;

[0136] The molten material is poured onto the surface of a metal block at room temperature for quenching to obtain a glassy material;

[0137] The glassy material was annealed at 850° C. for 5 hours to obtain a ninth sample.

[0138] The ninth sample was subjected to XRD analysis, and the results were as follows: Figure 2 As shown. Figure 2 It can be seen that the chemical formula of the ninth sample is mainly Li 1.4 Mg 0.2 Ge 1.8 P3O 12 , and contains some impurities.

[0139] The Li prepared in Example 3 and not annealed 1.4 Mg 0.2 Ge 1.8 P3O 12 The electrolyte glass sample was subjected to DSC test, and the test results were as follows Figure 3 As shown. It can be seen that the crystallization exothermic peak of this sample is at 610℃, indicating that Li 1.4 Mg 0.2 Ge 1.8 P3O 12 The crystal phase is formed at around 610℃.

[0140] The Li obtained in Example 4 1.6 Mg 0.3 Ge 1.7 P3O 12 (labeled as LMGP-03 in the figure) and the comparative sample Li 1.5 Al 0.5 Ge 1.5 P3O 12 (LAGP-05 in the figure) was subjected to solid-state nuclear magnetic resonance (SS-NMR) analysis. The test results are as follows Figure 4 , Figure 5 and Figure 6 shown.

[0141] from Figure 4 It can be seen that LMGP and LAGP have similar static 7 Li-NMR peak structure, both materials have high ionic conductivity.

[0142] from Figure 5 It can be seen that the lithium ions have similar site occupancy in LMGP and LAGP.

[0143] from Figure 6 It can be seen that LMGP is similar to LAGP, and Mg smoothly enters the LGP structure.

[0144] from Figures 4 to 6 It can be seen that the Mg element has been successfully incorporated into the LGP structure, and the occupancy of lithium ions in the resulting LMGP material is similar to that of LAGP (M1 and M2 occupancy, respectively).

[0145] The Li obtained in Example 4 1.6 Mg 0.3 Ge 1.7 P3O 12 Solid-state NMR 31 The P-MAS-NMR (room temperature) test curve is analyzed by peak separation. The test results are as follows Figure 7 As shown; for the comparative sample Li 1.5 Al 0.5 Ge 1.5 P3O 12 Solid-state NMR 31 The P-MAS-NMR (room temperature) test curve was analyzed by peak separation. The results are as follows Figure 8 As shown. Among them, Figure 7 The Pn (n=0, 1, 2) in the figure refers to different P and Mg linking structures. P0 means P(OGe)4 structure, P1 means P(OMg)(OGe)3, P2 means P(OMg)2(OGe)2, and V1 and V2 represent different glass states, which are not in the LMGP structure. Figure 8 In the figure, Pn refers to different P and Al linking structures, P0 means P(OGe)4 structure, P1 means P(OAl)(OGe)3, P2 means P(OAl)2(OGe)2, P3 means P(OAl)3(OGe), P′ and P″ represent Li4P2O7.

[0146] Combination Figures 7 and 8 It can be found that the form distribution of Al in LAGP is uniform, while the Mg element in LMGP mainly exists in the form of P(OMg)2(OGe)2. It can be seen that the structure of LMGP obtained in the embodiment of the present invention is different from that of LAGP.

[0147] The solid electrolyte Li of Example 3 (600°C), Example 6 (550°C), Example 7 (650°C), Example 8 (750°C) and Example 9 (850°C) 1.2 Mg 0.1 Ge 1.9 P3O 12 , X-ray diffraction (XRD) and solid state nuclear magnetic resonance (SS-NMR) tests were performed, and the test results were as follows Figure 2 and Fig. 9 Show.

[0148] from Figure 2 and Fig. 9 Combination Figure 1It can be seen that the structural incorporation of Mg into LGP only occurs at a relatively low sintering temperature (600°C to 650°C). Under higher sintering temperatures (750°C to 850°C), Mg exists in the electrolyte material in the form of interstitial impurities (interstitial magnesium oxides).

[0149] Application Example 1

[0150] A method for preparing a solid electrolyte membrane comprises the following steps:

[0151] The Li obtained in Example 3 1.4 Mg 0.2 Ge 1.8 P3O 12 Grind evenly, and mix with PEO and LiTFSI at a molar ratio of 0.5:18:1;

[0152] Then, 1 mL of acetonitrile solvent was added and stirring continued until uniform to obtain a jelly-like substance;

[0153] After the colloid is sealed, it is placed at 80°C for aging for 48 hours; the colloid is taken out and hot-pressed into a film using a hot press at a temperature of 80°C. The hot pressing is performed twice, wherein the pressure of the first hot pressing is maintained at 20 bar for 10 minutes, and the pressure of the second hot pressing is maintained at 25 bar for 5 minutes, to obtain a solid electrolyte membrane.

[0154] The solid electrolyte Li prepared in Example 3 1.4 Mg 0.2 Ge 1.8 P3O 12 (600°C sintering, LMGP), the solid electrolyte Li prepared in Example 9 1.4 Mg 0.2 Ge 1.8 P3O 12 The ionic conductivity of the solid electrolyte membrane (LMGP+PEO) prepared in Example 1 (sintered at 850°C, LGP+interstitial magnesium oxide) and the comparison sample LGP material was tested. The test results are as follows Fig.10 shown.

[0155] from Fig.10 It can be seen that the incorporation of Mg element helps to improve the ionic conductivity of LGP; however, when Mg element exists in the electrolyte material in the form of interstitial impurities (interstitial magnesium oxide), it cannot effectively improve the ionic conductivity of the material; using LMGP as an additive and mixing it with PEO, LiTFSI and other substances as a solid electrolyte membrane can more effectively improve the ionic conductivity of the material.

[0156] Application Example 2

[0157] A solid-state lithium battery comprises a lithium iron phosphate electrode sheet (as a positive electrode sheet), a lithium sheet (as a negative electrode sheet) and a solid electrolyte membrane obtained in Application Example 1, which are stacked in the manner of positive electrode sheet-solid electrolyte membrane-negative electrode sheet, so that the positive electrode sheet and the negative electrode sheet are separated by the solid electrolyte membrane, and assembled into a solid-state lithium battery.

[0158] The solid-state lithium battery assembled above was subjected to a battery cycle performance test at a cycle temperature of 60°C and a cycle rate of 0.1C. The test results are as follows: Fig.11 shown.

[0159] from Fig.11 It can be seen that the solid-state lithium battery has a higher discharge specific capacity at 60°C and exhibits better cycle performance, indicating that the solid-state electrolyte of the embodiment of the present invention is used as the electrolyte membrane, which is non-flammable and not only has higher safety performance, but also enables the solid-state lithium battery to have better cycle performance and high-temperature cycle performance.

[0160] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A solid electrolyte, characterized in that: The solid electrolyte has the following general formula: Li 1+2x Mg x Ge 2-x P3O 12 ; Among them, x takes any value from 0 to 0.5, and x does not take the value of 0; The solid electrolyte belongs to the trigonal crystal system, Ge and O are combined to form hexahedral GeO6, and Mg replaces part of Ge in the GeO6.

2. The solid electrolyte according to claim 1, characterized in that The solid electrolyte comprises: Li 1.1 Mg 0.05 Ge 1.95 P3O 12 , Li 1.2 Mg 0.1 Ge 1.9 P3O 12 , Li 1.4 Mg 0.2 Ge 1.8 P3O 12 , Li 1.6 Mg 0.3 Ge 1.7 P3O 12 , Li 2.0 Mg 0.5 Ge 1.5 P3O 12 Very little in the middle.

3. A method for preparing a solid electrolyte according to any one of claims 1 to 2, characterized in that: The following steps are involved: Mixing a lithium source, a magnesium source, a germanium source and a phosphorus source containing a phosphate group to obtain a first mixed material; The first mixed material is dried, and then heated to 400°C to 450°C at a heating rate of 3 to 8°C / min, and kept at 400°C to 450°C for 1 to 5 hours, and then heated to 1300°C to 1450°C at a heating rate of 5 to 20°C / min, and kept at 1300°C to 1450°C until the first mixed material is completely melted; Cooling to room temperature to obtain a glassy material; The glassy material is annealed to obtain a solid electrolyte.

4. The method for preparing a solid electrolyte according to claim 3, characterized in that: The lithium source, the magnesium source, the germanium source and the phosphate-containing phosphorus source are mixed according to a ratio of the amount of substance of lithium:magnesium:germanium:phosphate=k×(1+2x):x:(2-x):3, wherein x takes any value between 0 and 0.7, and x does not take the value of 0, and the coefficient k takes any value between 1 and 1.

1.

5. The method for preparing a solid electrolyte according to claim 3, characterized in that: The annealing temperature is 550°C to 1050°C; And / or, the cooling process is quenching.

6. The method for preparing a solid electrolyte according to claim 3, characterized in that: The annealing temperature is 600°C to 650°C.

7. The method for preparing a solid electrolyte according to any one of claims 3 to 6, characterized in that: The lithium source is selected from at least one of lithium carbonate, lithium hydroxide, lithium oxalate, lithium nitrate and lithium bicarbonate; The magnesium source is selected from at least one of magnesium carbonate, magnesium oxide, magnesium hydroxide, magnesium bicarbonate, magnesium acetate, and magnesium oxalate; The germanium source is selected from at least one of germanium dioxide, germanium monoxide, germanium tetrahydroxide, germanium nitrate, germanium oxalate, and germanium bicarbonate; The phosphate-containing phosphorus source is selected from at least one of diammonium phosphate, triammonium phosphate, diammonium hydrogen phosphate, phosphorus pentoxide, and phosphorus trioxide.

8. Use of the solid electrolyte as described in any one of claims 1 to 2 as a component of an all-solid-state lithium battery electrolyte membrane, a component of a lithium-ion battery separator coating, or an additive for the positive and / or negative electrodes of an all-solid-state lithium battery.

Citation Information

Patent Citations

  • Ceramic solid electrolyte and preparation method thereof

    CN105406118A

  • Production method of sulfide solid electrolyte material, and sulfide solid electrolyte material

    JP2013037897A

  • All-solid type secondary battery, solid electrolytic composition, battery electrode sheet arranged by use thereof, manufacturing method of battery electrode sheet, and manufacturing method of all-solid type secondary battery

    JP2016035911A

  • Sulfide solid electrolyte material, battery, and producing method for sulfide solid electrolyte material

    US20150357673A1